(untitled) (The Agriculturists, 2017)
An experiment was conducted at Bangladesh Rice Research Institute (BRRI) Farm at Rangpur during July 2014 - June 2016 to introduce a 4-crops pattern with the aim of increasing cropping intensity, productivity, income and soil fertility. The experimental design was RCB with 3 replications. Four cropping patterns were tested which were: CP1 = T. Aman (BRRI dhan62)-Potato (Cardinal)-Mungbean (BARI Mung-6)-T. Aus (BRRI dhan48), CP2 = T. Aman (BRRI dhan62)-Mustard (BARI Sorisha-14)-Mungbean (BARI Mung-6)-T. Aus (BRRI dhan48), Farmers improved practice (FIP) = T. Aman (BR11)-Potato (Cardinal)-Maize (NK 40) and Farmers general practice (FP) = T. Aman (BR11)-Boro (BRRI dhan28)- Fallow. In T. Aman 2014, BRRI dhan62 produced 3.87 and 3.85 t ha-1 grain yields under CP1 & CP2 (4 crops systems), respectively; BR11 gave grain yield of 4.62 and 4.36 t ha-1 in FIP and FP (3 and 2 crop system), respectively. In T. Aman 2015, BRRI dhan62 produced grain yield of 4.23 and 4.19 t ha-1 in CP1 and CP2, and BR11 gave grain yield of 5.95 and 5.92 t ha-1 in FIP and FP, respectively. After T. Aman, potato yield was 24.66 t ha-1 in CP1 and 24.17 t ha-1 in FIP during 2014-15. In CP2, 2nd crop mustard yield was 1.16 t ha-1 and3rd crop mungbean yield was only 0.98 t ha-1.In CP1, 3rd crop mungbean yield was only 0.83 t ha-1. After potato in FIP, maize yield was 8.38 t ha-1. After T. Aman (BR11) in FP, grain yield of BRRI dhan28 was 5.42 t ha-1. The yield of BRRI dhan48 in CP1 and CP2 (as 4th crop) was 4.5 t ha-1. Similar results of different crops were obtained in 2015-16. The rice equivalent yield (REY) was found to be 30.05 & 35.95 t ha-1yr-1 in CP1 during 1st and 2nd yearfollowed by FIP (23.92 & 29.82 t ha-1yr-1, respectively). The REY was higher in 2nd year compared to 1st year. In 2014-15 the highest net return of Tk.2,42,560 ha-1 was observed in CP1 followed by FIP(Tk.1,58,380 ha-1); in 2015-16, the highest net return was in CP1 (Tk.2,16,960 ha-1) followed by FIP(Tk.1,24,620 ha-1). Potato based cropping pattern was thus, the most suitable and profitable pattern in this area. T. Aman (BRRI dhan62)-Potato (Cardinal)-Mungbean (BARI Mung-6)-T. Aus (BRRI dhan48) may, therefore, be the most suitable and profitable cropping pattern in medium high lands of Rangpur region. The Agriculturists 2017; 15(1) 116-126